Optimal Dosing of Prophylactic Enoxaparin after Surgical Procedures: Results of the Double-Blind, Randomized, Controlled FIxed or Variable Enoxaparin (FIVE) Trial. Issue 4 (April 2021) - Pannucci, Christopher J.; Fleming, Kory I.; Bertolaccini, Corinne; Agarwal, Jayant; Rockwell, W. Bradford; Mendenhall, Shaun D.; Kwok, Alvin; Goodwin, Isak; Gociman, Barbu; Momeni, Arash
Abstract : Background: The accepted "one-size-fits-all" dose strategy for prophylactic enoxaparin may not optimize the medication's risks and benefits after surgical procedures. The authors hypothesized that weight-based administration might improve the pharmacokinetics of prophylactic enoxaparin when compared to fixed-dose administration. Methods: The FIxed or Variable Enoxaparin (FIVE) trial was a randomized, double-blind trial that compared the pharmacokinetic and clinical outcomes of patients assigned randomly to postoperative venous thromboembolism prophylaxis using enoxaparin 40 mg twice daily or enoxaparin 0.5 mg/kg twice daily. Patients were randomized after surgery and received the first enoxaparin dose at 8 hours after surgery. Primary hypotheses were (1) weight-based administration is noninferior to a fixed dose for avoiding underanticoagulation (anti–factor Xa <0.2 IU/ml) and (2) weight-based administration is superior to fixed-dose administration for avoiding overanticoagulation (anti–factor Xa >0.4 IU/ml). Secondary endpoints were 90-day venous thromboembolism and bleeding. Results: In total, 295 patients were randomized, with 151 assigned to fixed-dose and 144 to weight-based administration of enoxaparin. For avoidance of under anticoagulation, weight-based administration had a greater effectiveness (79.9 percent versus 76.6 percent); the 3.3 percent (95 percent CI, –7.5 to 12.5 percent) greater effectiveness achieved statistically significant noninferiority relative to the a priori specified −12 percent noninferiority margin ( p = 0.004). For avoidance of overanticoagulation, weight-based enoxaparin administration was superior to fixed-dose administration (90.6 percent versus 82.2 percent); the 8.4 percent (95 percent CI, 0.1 to 16.6 percent) greater effectiveness showed significant safety superiority ( p = 0.046). Ninety-day venous thromboembolism and major bleeding were not different between fixed-dose and weight-based cohorts (0.66 percent versus 0.69 percent, p = 0.98; 3.3 percent versus 4.2 percent, p = 0.72, respectively). Conclusion: Weight-based administration showed superior pharmacokinetics for avoidance of underanticoagulation and overanticoagulation in postoperative patients receiving prophylactic enoxaparin. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, I. Abstract : Supplemental Digital Content is available in the text.